Comparative analysis of heat transfer dynamics in high-intensity focused ultrasound and microwave ablation for cancer treatment - Teerapot Wessapan; Pornthip Keangin; Phadungsak Rattanadecho; Nisakorn Somsuk (International Journal of Thermofluids)
This study addresses the crucial need for comparative analyses of High-intensity Focused Ultrasound (HIFU) and Microwave Ablation (MWA) as effective and minimally invasive cancer treatment techniques. Both modalities employ thermal ablation mechanisms but differ fundamentally in their operational physics: HIFU uses focused acoustic waves and MWA uses electromagnetic radiation. Utilizing advanced numerical simulations based on porous media theory, we modeled acoustic and electromagnetic wave propagation and their subsequent interactions with biological tissues. This approach enabled us to accurately depict and analyze the temperature distributions and fluid dynamics during treatment scenarios. Significant results highlighted fundamental differences in the heat transfer mechanisms between the two techniques: for example, under similar power settings, HIFU's focal region reached peak temperatures approximately 2–4 °C higher within the first 10 s, while MWA's thermal footprint extended 20–30 % farther radially. HIFU demonstrated precise, localized heating at the acoustic focus, whereas MWA exhibited broader thermal effects owing to its electromagnetic wave spread. Key findings demonstrate that HIFU provides precision in thermal applications at the risk of requiring exact transducer alignment, whereas MWA's extensive heat spread could treat larger or irregularly shaped tumors but might affect adjacent tissues. Moreover, the flow effects due to the porous nature of tissues significantly influence the heat distribution patterns, with HIFU generating localized and intense heat flux owing to focused acoustic streaming, whereas MWA promotes wider heat spread facilitated by natural convection flows.